Utilization of the Lampung Museum as a Learning Resource of Historical Learning at Senior High School: Pemanfaatan Museum Lampung sebagai Sumber Belajar Pembelajaran Sejarah di Sekolah Menengah Atas - Fadli, Muhammad Rijal; Acim, Acim (Pedagogia : Jurnal Pendidikan, 2022)
This study aims: (1) to know Lampung museum collections that can be used as a learning resource historical learning in Metro 2 State Senior High School; (2) Utilization of the Lampung museum as a learning resource historical learning in Metro 2 State Senior High School; (3) Constraints faced in the use of the Lampung museum as a learning resource historical learning. The research method used is the qualitative descriptive analysis of Milles and Hubermans models. Data collection techniques used were observation, in-depth interviews, and documentation. Data analysis is data reduction, data display, and data verification. The results showed that the Lampung museum collection was divided into 10 categories, namely geology, biology, ethnography, archeology, history, numismatics, philology, ceramics, fine arts, and technology, from all the collections can be used as a learning resource historical learning. The utilization of the Lampung museum as a learning resource historical learning has been carried out but not fully maximized. Lampung museum collections are used as a source of learning history by adjusting to the Competency Standards and Basic Competence curriculum for historical subjects. The implementation of history learning makes the Lampung museum as a source of learning done by the method of study visits.